Cyclical aging tests in latex coating with TiO2 nanoparticles by UVb radiation - Fernandez-Vivanco, Jenny Miriam; Jiménez-Calderón, César Eduardo; Guzman-Duxtan, Aldo Javier; Levano-Huamaccto, Carlos Alberto (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study evaluated the properties of adhesion, cracking, rusting, and accumulated irradiance on the surface of four vinyl acrylic resin coatings. QUV accelerated aging technique was applied. The coatings accumulated irradiance in cyclic form and was controlled by the tests of atmospheric temperature and relative humidity. A paper money currency validator counterfeit has been used because of its constant irradiance of 1,41 mW/cm2 ; a power of 9 W of UV radiation; 220 V, ranging an equipment temperature (OPALUX) between 40 °C and 60 °C. Irradiance has been measured by using the UV light meter equipment model YK-35UV (2 to 20 mW/cm2 ). Latex coatings embedded with TiO2 nanoparticles and prepared in four different formulations with CaCO3 plus Diatomite were applied on a surface area of 5.5 cm length times 1.5 cm width. The exposition time ranged from 56 to 500 h of irradiance at a period span of eight h each day. Coatings were altered on its properties of adhesion, elasticity and photooxidation on their surface.